Ocean babies - McCurry, Kristen. frey50; Jackson, Aimee (Chanhassen, Minn. : NorthWord Press, 2004)
Simple text and color photographs describe baby animals that live in the water.
87202
Keywords: Marine animals -- Infancy -- Juvenile literature; Marine animals -- Infancy; ANIMALS -- INFANCY; Pink Check